Population levels and geographical distribution of HIV RNA in rural Ugandan and Kenyan communities, including serodiscordant couples: a cross-sectional analysis. Issue 3 (March 2017) - Jain, Vivek; Petersen, Maya L; Liegler, Teri; Byonanebye, Dathan M; Kwarisiima, Dalsone; Chamie, Gabriel; Sang, Norton; Black, Doug; Clark, Tamara D; Ladai, Andras; Plenty, Albert; Kabami, Jane; et al.
Summary: Background: As sub-Saharan Africa transitions to a new era of universal antiretroviral therapy (ART), up-to-date assessments of population-level HIV RNA suppression are needed to inform interventions to optimise ART delivery. We sought to measure population viral load metrics to assess viral suppression and characterise demographic groups and geographical locations with high-level detectable viraemia in east Africa. Methods: The Sustainable East Africa Research in Community Health (SEARCH) study is a cluster-randomised controlled trial of an HIV test-and-treat strategy in 32 rural communities in Uganda and Kenya, selected on the basis of rural setting, having an approximate population of 10 000 people, and being within the catchment area of a President's Emergency Plan for AIDS Relief-supported HIV clinic. During the baseline population assessment in the SEARCH study, we did baseline HIV testing and HIV RNA measurement. We analysed stable adult (aged ≥15 years) community residents. We defined viral suppression as a viral load of less than 500 copies per mL. To assess geographical sources of transmission risk, we established the proportion of all adults (both HIV positive and HIV negative) with a detectable viral load (local prevalence of viraemia). We defined transmission risk hotspots as geopolitical subunits within communities with an at least 5% local prevalence of viraemia. We also assessed serodiscordant couples, measuring the proportion of HIV-positive partners with detectable viraemia. The SEARCH study is registered withClinicalTrials.gov, numberNCT01864603 . Findings: Between April 2, 2013, and June 8, 2014, of 303 461 stable residents, we enumerated 274 040 (90·3%), of whom 132 030 (48·2%) were adults. Of these, 117 711 (89·2%) had their HIV status established, of whom 11 964 (10·2%) were HIV positive. Of these, we measured viral load in 8828 (73·8%) people. Viral suppression occurred in 3427 (81·6%) of 4202 HIV-positive adults on ART and 4490 (50·9%) of 8828 HIV-positive adults. Regional viral suppression among HIV-positive adults occurred in 881 (48·2%) of 1827 people in west Uganda, 516 (45·0%) of 1147 in east Uganda, and 3093 (52·8%) of 5854 in Kenya. Transmission risk hotspots occurred in three of 21 parishes in west Uganda and none in east Uganda and in 24 of 26 Kenya geopolitical subunits. In Uganda, 492 (2·9%) of 16 874 couples were serodiscordant: in 287 (58·3%) of these couples, the HIV-positive partner was viraemic (and in 69 [14·0%], viral load was >100 000 copies per mL). In Kenya, 859 (10·0%) of 8616 couples were serodiscordant: in 445 (53·0%) of these couples, the HIV-positive partner was viraemic (and in 129 [15%], viral load was >100 000 copies per mL). Interpretation: Before the start of the SEARCH trial, 51% of east African HIV-positive adults had viral suppression, reflecting ART scale-up efforts to date. Geographical hotspots of potential HIV transmission risk and detectable viraemia among serodiscordant couples warrant intensified interventions. Funding: National Institute of Allergy and Infectious Diseases (National Institutes of Health) and the President's Emergency Plan for AIDS Relief.